Scenario Planning of Sub-District Proliferation Using Cost and Benefit Analysis (CBA) in Tambraw Regency - Rohmadin, Sulthon; Batubara, Yusi Eva (Jurnal Multidisiplin Madani, 2023)
Limited government budgets are a common problem faced in various countries. The Government is faced with multiple community demands that must be met. This causes the Government to be careful in determining priority programs. In deciding the feasibility of a project related to the public sector, the Government faces many considerations and problems, including sub-districts proliferation. One analysis that can be used as a tool to select programs that are worthy of priority is to use cost and benefit analysis. This research aims to disseminate an understanding of cost and benefit analysis to local government officials, especially in Tambraw Regency. This research uses an exploratory research method with a qualitative approach. The analysis method in this research is the scenario planning method; the stages consist of strategic analysis, scenario creation, strategy finding, and strategy formulation